Q: What is -y - 4 2y 11?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2

4y+4 = 2y+12 4y-2y = 12-4 2y = 8 y = 4

x - 2y = 4 Add 2y to both sides: x = 4 + 2y Subtract 4 from both sides: x - 4 = 2y Divide both sides by 2: (x - 4)/2 = y or y = 0.5x - 2

√(2y) + 3 = 11 √(2y) = 11 - 3 = 8 √2 x √y = 8 √y = 8/√2 y = (8/√2)2 = 64/2 = 32

4y + 4 = 2y + 12Subtract 2y from each side of the equation:2y + 4 = 12Subtract 4 from each side:2y = 8Divide each side by 2:y = 4

Related questions

If: 2Y+3 = 11 then the value of Y is 4

2

If you mean: -3x + y = 1 5x + 2y = 4 You must replace one letter, for example y, so it gives you an equation only using x. If you bring everything to one side on the bottom equatin, it would read: y = (4 - 5x)/2 Now use this equation to replace the y on the first equation: -3x + (4-5x)/2 = 1 and solve for x Find a common denominator, which is 2... (-6x)/2 + (4-5x)/2 = 1 Combine... (-6x + 4 - 5x) / 2 =1 which is: (-11x + 4) / 2 = 1 Bring the 2 to the other side... -11x + 4 = 2 Bring the 4 to the other side... -11x = -2 Bring the -11 to the other side... x = -2 / -11 or 2/11 Now plug in this number for x to solve for y: 5x + 2y = 4 5(2/11) + 2y = 4 10/11 + 2y = 4 2y = 4 - (10/11) common denominator is 11 so, 2y = 44/11 - 10/11 2y = 34/11 divide by 2 y = 34/11 * 1/2 y = 34/22 simplify y = 17/11 x = 2/11 y = 17/11 If you replace both letters in the top equations with these answers, both sides should equal each other.

Solution: 2y + 4 = 3 + y Combine like terms: 2y - y = 3 - 4 Simplify further: y = -1

2y2-2y-4 = (2y-4)(y+1) when factored

4y+4 = 2y+12 4y-2y = 12-4 2y = 8 y = 4

-8

-2X + 2Y = 4 2Y = 2X + 4 Y = X +2 by inspection, 2 but, you could also 0 out X in original equation -2(0) + 2Y = 4 2Y = 4 Y = 2

x - 2y = 4 Add 2y to both sides: x = 4 + 2y Subtract 4 from both sides: x - 4 = 2y Divide both sides by 2: (x - 4)/2 = y or y = 0.5x - 2

If Y and y are the same, then it is -y + 4 or 4 - y.

√(2y) + 3 = 11 √(2y) = 11 - 3 = 8 √2 x √y = 8 √y = 8/√2 y = (8/√2)2 = 64/2 = 32

8y+4-2y=22